Puritanism, male gaze and female spectator: "The Scarlet Letter" (2018), by Angélica Liddell - Oñoro Otero, Cristina (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
In this article, I aim to address Angélica Liddell’s production of The Scarlet Letter, a free adaptation of Nathaniel Hawthorne’s novel which premiered in France in 2018, from the perspective of ‘the feminist spectator’ (Dolan). I will examine the paradoxical emotions which such spectator experiences during a play in which women and the puritanism associated with the #MeToo movement are attacked; whilst, at the same time, from an aesthetic point of view, the ‘dominant male gaze’ (Mulvey) is challenged, therefore reinforcing Liddell as a creator. As it will be shown, Liddell’s work reclaims the theatrical performance as a ritualistic space of intimacy, in opposition to the puritan and hypocritical media culture of globalised behaviour. Ultimately, through Liddell’s production, we can approach the conflictive way in which the spectator is regarded by part of contemporary performing creators.